The Density of Aedes aegypti Larvae Density and the Incidence of Dengue Hemorrhagic Fever in the Pesingahan Environment, Pagesangan Barat Village, Mataram - Urip, Urip; Rizki, Kurnia; Tatontos, Erlin Yustin; Gunarti, Gunarti; Kholik, Kholik (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Dengue hemorrhagic fever remains a public health concern in West Nusa Tenggara Province, with the majority of cases occurring in Mataram City and the Pesinggahan Environment of West Pagesangan Village. The density of Aedes aegypti larvae as disease vectors has a strong influence on the high incidence of cases and the spread of dengue hemorrhagic fever. The objective of this study was to identify if there was a relation between the density of Aedes aegypti larvae and the rate of dengue hemorrhagic fever in the Pesinggahan Environment of Pagesangan Barat Village. This study is an analytic observational study with a cross-sectional design. This study's sample size was 56 houses. The data collected included information on the density of Aedes aegypti larvae and the incidence rate of dengue hemorrhagic fever in the Pesinggahan Environment of Pagesangan Barat Village over the previous year. Descriptive analysis was used to examine data on the density of Aedes aegypti larvae and the incidence rate of dengue hemorrhagic fever in the Pesinggahan environment. The findings revealed that the density of Aedes aegypti larvae was high (Density Figure (DF) = 6), as was the incidence rate of dengue hemorrhagic fever (0.39%). The statistical analysis between the density of A. aegypti larvae and the incidence rate of dengue hemorrhagic fever in the Pesinggahan Environment with the chi square test demonstrated indicate that p-value = 0.000 < alpha = 0.05. Based on the results of the study, there was a relationship between the density of A. aegypti larvae and the incidence rate of dengue hemorrhagic fever in Pesinggahan, Pagesangan Barat Village. Further research is required regarding the detection of the dengue virus transmitted by A. aegypti mosquitoes to their offspring (transovarial).